(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A network connecting mobile nodes wirelessly is known as MANET. In MANET the communication takes place with the help of mobile nodes. Using the wireless connection, mobile devices are connected and the nodes freely move where it wants to share information with each other. MANET’s are dynamic in nature and do not have fixed infrastructure to control nodes in the networks. Wireless ad hoc networks has various characteristics like dynamic topology, limited resources, absence of central controller etc. Every node in a MANET forwards data so that it can reach to its destination. . All nodes are involved in packet forwarding in order to cooperate with each node. Suppose, if the nodes are not transferring the packets to its neighbor nodes it is called as selfish nodes. Considering all the features of MANET, nodes in MANET work on the principle of co-operating with other nodes in network to help in various activities of the network like successful transfer data from source to destination. Some nodes in the network take advantage of co-operation and pretend to be co-operating with other nodes however they are saving on their resources like battery and drop the data whenever they receive it without sending it to the required destination or intermediate nodes to the destination. Route discovery and packets forwarding consumes bandwidth and energy. A kind of routing misbehavior of node is few nodes may be act as selfish by taking part in finding route and upkeep process, but deny forwarding the packet. Such type of misbehavior reduce packet transfer ratio and also degrade system performance in terms of power and bandwidth. MANETs is lack in centralized monitoring and infrastructure less behavior makes it more vulnerable to attack, and difficult to detect selfish node effectively. The selfish node behavior presence leads to partition the network and makes an negative impact in the operation of the network.